2005
DOI: 10.1038/ni1210
|View full text |Cite
|
Sign up to set email alerts
|

Stable T cell–dendritic cell interactions precede the development of both tolerance and immunity in vivo

Abstract: The maturation status of dendritic cells (DCs) determines whether they prime or tolerize T cells. We targeted ovalbumin peptide exclusively to DCs in situ using an antibody to DEC-205 and studied the interaction of DCs with naive CD4(+) T cells in tolerizing or priming conditions. We used two-photon microscopy to simultaneously track antigen-specific OT-II T cells, nonspecific T cells and DCs in lymph nodes of living mice. In both tolerance and immunity, OT-II cells arrested on DCs near high endothelial venule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
301
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(318 citation statements)
references
References 48 publications
16
301
1
Order By: Relevance
“…DCs in these mice exhibit high Xuorescence, and are readily identiWable by both Xuorescence microscopy and Xow cytometry. These mice have not only greatly improved our understanding of the behavior of endogenous DCs in the LN (Lindquist et al 2004;Shakhar et al 2005), but also their roles in various models of infection (Aoshi et al 2008;Hapfelmeier et al 2008;Veres et al 2007). They also enabled the visualization of intestinal DCs (Flores-Langarica et al 2005) and the identiWcation of a previously uncharacterized population of DCs in the brain (Bulloch et al 2008).…”
Section: Lcs and Ddcs In The Skin In Vivo: Lessons From Confocal Micrmentioning
confidence: 99%
“…DCs in these mice exhibit high Xuorescence, and are readily identiWable by both Xuorescence microscopy and Xow cytometry. These mice have not only greatly improved our understanding of the behavior of endogenous DCs in the LN (Lindquist et al 2004;Shakhar et al 2005), but also their roles in various models of infection (Aoshi et al 2008;Hapfelmeier et al 2008;Veres et al 2007). They also enabled the visualization of intestinal DCs (Flores-Langarica et al 2005) and the identiWcation of a previously uncharacterized population of DCs in the brain (Bulloch et al 2008).…”
Section: Lcs and Ddcs In The Skin In Vivo: Lessons From Confocal Micrmentioning
confidence: 99%
“…It was during this phase that T cell divisions became detectable [28]. These findings were essentially confirmed for CD4 + T cell activation in vivo [52] and in an explanted lymph node model [50]. In addition, the group of Amigorena showed that CD8 + T cells contacting DC under a regime inducing tolerance rather that activation displayed short-lived interactions at any time point, while Mempel's three phase model with long interactions in a middle phase [28] could be confirmed for an activatory situation [77].…”
Section: The Road To Intravital Imaging -Phase Models Of T Cell Activsupporting
confidence: 71%
“…3, [28,[47][48][49][50]). When a firm contact is established, the T cell can give up its migratory morphology and round up again or remain stationary [51,52]. However, it may also maintain a dynamic state of motility and crawl along the APC surface with substantial velocities of up to 10 µm per minute [28,34,49,53].…”
Section: The Biophysics Of T Cell Activationmentioning
confidence: 99%
“…track velocity, displacement, meandering index, motility co-efficient. 4. It is also possible to measure the interaction between DC and T cell using the colocalization tool to identify green and red voxels.…”
Section: Discussionmentioning
confidence: 99%